1980
DOI: 10.1111/j.1432-1033.1980.tb04881.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoenzymic Studies on the Transition‐State Analog Complex Creatine Kinase ‐ ADPMg ‐ Nitrate ‐ Creatine

Abstract: Concomitant with the formation of the transition state analog complex creatine kinase . ADPMg . nitrate . creatine [Milner-White, E. J. and Watts, D. C. (1971) Bioclzem. J. 122, 727-7401 there results a large difference spectrum. The shape of the spectrum was characteristic of tryptophan exposure.The kinetics of formation and final amplitude of the spectrum were studied at -15 "C using a stopped-flow apparatus. The results obtained allowed for a plausible reaction pathway for nitrate fixation: the ordered add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…An extremely stable complex can be formed with creatine, CK, MgADP and with some type of anion as NO, (MilnerWhite and Watts, 1971 ;Watts, 1973). This complex called the transition-state-analog complex of CK, can be viewed as an intermediate state in the phosphoryl transfer (Travers and Barman, 1980). Therefore any structural information gained about this transition-state analog could provide more insights into the enzymic mechanism of phosphoryl transfer in CK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An extremely stable complex can be formed with creatine, CK, MgADP and with some type of anion as NO, (MilnerWhite and Watts, 1971 ;Watts, 1973). This complex called the transition-state-analog complex of CK, can be viewed as an intermediate state in the phosphoryl transfer (Travers and Barman, 1980). Therefore any structural information gained about this transition-state analog could provide more insights into the enzymic mechanism of phosphoryl transfer in CK.…”
Section: Resultsmentioning
confidence: 99%
“…suggested by ultraviolet spectroscopic and kinetic studies that the conformation of the transition-state-analog complex was very similar than the conformation of the transition-state complex on the catalytic pathway (Travers and Barman, 1980). Therefore any structural alteration of the transition-state-analog complex could provide some clues into the catalytic mechanism.…”
Section: Adp Binding To Transition-state-analog Complex It Has Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition-analog complex can be considered as a transition state of the catalytic pathway (Travers and Barman, 1980;Balny et al, 1985) and therefore can provide more insight into the molecular mechanism of phosphoryl transfer. The RIDS of the nicked-CK .…”
Section: Resultsmentioning
confidence: 99%
“…The changes of ultraviolet absorption spectra of CK produced by the addition of ATP or ADP (with or without creatine and nitrate), suggested that a Trp residue is near the active site (Roustan et al, 1968;Travers and Barman, 1980;Balny et al, 1985). Based on the rotatory dispersion spectra of complexes of CK with ATP or ADP (Kagi et al, 1971), it was proposed that the large Cotton effect observed was caused by the stacking of the adenine purine moiety with one aromatic group of the enzyme.…”
mentioning
confidence: 99%